2010
DOI: 10.1007/s12035-010-8142-4
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3γ and Neuroglobin are New Intrinsic Protective Factors for Cerebral Ischemia

Abstract: A number of intrinsic factors are present intracellularly and could be turned on to protect cells from stress and injury, including cerebral ischemia. The degree of protection of these factors is dependent on the time of induction, their concentration, as well as the duration and extent of injury. This review summarizes recent studies on some of the protective factors with specific emphasis on two recently discovered intrinsic protective proteins: 14-3-3gamma protein and neuroglobin. Both of them were original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 122 publications
1
20
0
Order By: Relevance
“…41 In neurons, 14-3-3γ protein appears to contribute to neuronal vulnerability during oxidative stress 42 and increased levels promote astrocyte survival, whereas decreased levels result in increased apoptotic loss under ischemia. 43 YWHAG resides on chromosome 7q11.23, along with several genes, and haploinsufficiency of this region results in William–Beuren syndrome, which includes a specific mental retardation profile, distinctive dysmorphic features and supravalvular aortic stenosis. 44 Interestingly, zebrafish knocked down for YWHAG have reduced brain size and an increased diameter of the heart tube.…”
Section: Discussionmentioning
confidence: 99%
“…41 In neurons, 14-3-3γ protein appears to contribute to neuronal vulnerability during oxidative stress 42 and increased levels promote astrocyte survival, whereas decreased levels result in increased apoptotic loss under ischemia. 43 YWHAG resides on chromosome 7q11.23, along with several genes, and haploinsufficiency of this region results in William–Beuren syndrome, which includes a specific mental retardation profile, distinctive dysmorphic features and supravalvular aortic stenosis. 44 Interestingly, zebrafish knocked down for YWHAG have reduced brain size and an increased diameter of the heart tube.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is well known that astrocytes and neurons respond differently to ischemic insults via distinct mechanisms. 10 Theoretically, protecting all types of brain cells simultaneously is required for stroke treatment. 2 Thus, finding the key protective molecules conserved in brain cells and understanding clearly their protective mechanisms is required for future development of effective cytoprotective drugs and treatments.…”
mentioning
confidence: 99%
“…9). There is growing interest in Ywhag as a mediator of neuroprotection in cerebral ischemia (Dong et al 2010) and the observed decrease in its expression is consistent with the activation of cell death pathways. Additionally, up-regulation of Ywhaq has been observed in amyotrophic lateral sclerosis patients (Malaspina et al 2000), and has been found to be necessary for autophagy (Wang et al 2010).…”
Section: Interaction Network Analysismentioning
confidence: 90%